Odpowiedź:
g) 10 - 1 i 5/6 : 4 i 1/2= 10- 11/6: 9/2= 10 - 11/6*2/9( skracamy 6 i 2 przez 2)=
= 11/3*1/9= 11/27
b) 1 i 1/2 - 3/4 + 5/8= 1 i 4/8 - 6/8 +5/8= 12/8- 6/8+5/8= 6/8+5/8= 11/8= 1 i 3/8
e) 7/9: 2/3 *6/7= 7/9*3/2 *6/7( skracamy 7 i 7 przez 7, oraz 9 i 3 przez 3, oraz
6 i 2 przez 2)= 1/3*3= 3/3=1
h) 5/7 *4 i 2/3 +5/6 : 1 i 1/9= 5/7*14/3 + 5/6: 10/9 ( ( skracamy 7 i 14 przez 7)=
= 5*2/3 + 5/6*9/10( skracamy 5 i 10 przez 5, oraz 6 i 9 przez 3)=
=10/3+ 3/4= 3 i 1/3+ 3/4= 3 i 4/12+ 9/12= 3 i 13/12= 4 i 1/12
i) ( 2 i 1/4 - 1 i 2/3) : ( 1/6+ 2/9)= ( 2 i 3/12-1 i 8/12): ( 3/18 +4/18)=
= ( 1 i 15/12-1 i 8/12): 7/18= 7/12: 7/18= 7/12*18/7( skracamy 7 i 7 przez 7,
oraz 12 i 18 przez 6) = 1/2*3= 3/2= 1 i 1/2
Szczegółowe wyjaśnienie: